A prospective study of collapsing focal segmental glomerulosclerosis. (2nd July 2016) - Raja, Ramachandran; Nada, Ritambhra; Yadav, Ashok K.; Kumar, Ashwani; Goyal, Ajay; Kumar, Vivek; Rathi, Manish; Kohli, H. S.; Gupta, K. L.; Sakhuja, Vinay; Jha, Vivekanand
Abstract: Collapsing focal segmental glomerulosclerosis (cFSGS) is characterized by rapid progression to end-stage renal disease (ESRD). We evaluated the clinicopathological spectrum of cFSGS and compared its clinical behavior to steroid and tacrolimus (TAC)-resistant noncollapsing focal segmental glomerulosclerosis (FSGS). All patients (>14 years) diagnosed with cFSGS were enrolled in the study. Staining for differentiated podocyte markers such as WT 1, PAX and KI67 were performed in all patients. The outcome and histological features of cFSGS was compared with a prospectively followed cohort of steroid and TAC-resistant noncollapsing FSGS. The study included 22 cFSGS patients and 19 cases of steroid and TAC-resistant FSGS. Complete remission, partial remission, steroid resistance, progression to ESRD and death were observed in 13.6%, 4.5%, 27.3%, 36.4% and 18.2% patients, respectively. Patients with cFSGS had higher serum creatinine and more advanced tubulointerstitial changes compared to resistant FSGS. Twenty-six percent of therapy resistant noncollapsing FSGS progressed to ESRD after two years of stopping TAC. However, there was no difference in progression to ESRD between cFSGS and therapy-resistant noncollapsing FSGS at the end of two years. Glomerular collapse in the setting of FSGS is poorly responsive to treatment and has a high rate of progression to ESRD. The long-term prognosis of cFSGS and steroid and TAC-resistant FSGS are similar.